2017
DOI: 10.5194/acp-2017-676
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impacts of Different Characterizations of Large-Scale Background on Simulated Regional-Scale Ozone Over the Continental United States

Abstract: Abstract. This study analyzes simulated regional-scale ozone burdens both near the surface and aloft, estimates process contributions to these burdens, and calculates the sensitivity of the simulated regional-scale ozone burden to several key model 15 inputs with a particular emphasis on boundary conditions derived from hemispheric or global scale models. The Community Multiscale Air Quality (CMAQ) model simulations supporting this analysis were performed over the continental U.S. for the Hypothetical bounding… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…Studies based on chemical transport models (CTMs) have shown that air quality in the U.S. can be considerably influenced by pollutants beyond the U.S. boundaries, such as through intercontinental transport, and through stratosphere-totroposphere exchange (Zhang et al, 2011;Lin et al, 2012;Nopmongcol et al, 2016;Langford et al, 2017;Lin et al, 2017;Hogrefe et al, 2017;Mathur et al, 2017). Similar findings have also been reported based on routine observations and field 5 campaign measurements (e.g.…”
Section: Introductionsupporting
confidence: 64%
“…Studies based on chemical transport models (CTMs) have shown that air quality in the U.S. can be considerably influenced by pollutants beyond the U.S. boundaries, such as through intercontinental transport, and through stratosphere-totroposphere exchange (Zhang et al, 2011;Lin et al, 2012;Nopmongcol et al, 2016;Langford et al, 2017;Lin et al, 2017;Hogrefe et al, 2017;Mathur et al, 2017). Similar findings have also been reported based on routine observations and field 5 campaign measurements (e.g.…”
Section: Introductionsupporting
confidence: 64%